La production de l’ignorance en matière de dangers professionnels est-elle un processus cognitif uniquement contrôlé par le patronat ? - Stéphane Le Lay (Revue d'anthropologie des connaissances)
Based on a critical discussion of Pascal Marichalar’s book, Qui a tué les verriers de Givors?, this article aims to highlight the value of taking into account the subjective dimension that workers bring into their activities, for agnotology researches about health problems in the workplace. With psychodynamics of work, it appears that the agnotology of occupational hazards inside the industrial glassware in Givors is not just a matter of employers deliberately trying to conceal a certain amount of information from the glassmakers: it is likely to also be the result of occupational practices specific to these workers, developed as a coping strategy to preserve their mental health. By ignoring this pathic dimension, agnotology analyses provide a partial and distorted description of professional realities and the collective movements that are rooted in them.